GENETIC VARIABILITY, CORRELATION AND PATH COEFFICIENT ANALYSIS OF YIELD AND QUALITY TRAITS IN PUMPKIN (Cucurbita moschata Duch ex Poir.) (Bangladesh Journal of Plant Breeding and Genetics, 2013)
The experiment was conducted to study variability, correlation coefficient and path analysis for yield and quality related traits of 30 pumpkin genotypes. Significant variations were found among the genotypes for most of the characters studied. High genotypic coefficient of variation (GCV) and high heritability coupled with high genetic advance in percent of mean were observed for beta-carotene followed by non-reducing sugar, number of seeds per fruit, yield per plant, dry weight, flesh thickness, number of male flowers per plant and number of female flowers per plant which indicated that these characters were under additive gene control and selection for genetic improvement for these traits might be effective. Correlation co-efficient between yield per plant with number of primary branches, number of fruits per plant and single fruit weight were positive and highly significant. On the other hand, days to first female flower, number of male flowers per plant, ß- carotene and total sugar showed positive and insignificant correlation with yield per plant. But correlation between brix content and yield per plant were significantly negative. Path coefficient analysis revealed that the maximum direct contribution towards yield was obtained through number of fruits per plant followed by days to first female flower and single fruit weight indicated that these traits should be considered as primary components of yield. Negative direct effect on yield was exerted by total sugar followed by number of female flowers per plant, reducing sugar and brix content. Considering all the qualitative and quantitative traits ten genotypes as G7, G13, G14, G17, G18, G19, G20, G22, G27, G29 among thirty were selected and suggested to be selfed for the development of inbred line for use in future breeding programme.DOI: http://dx.doi.org/10.3329/bjpbg.v26i1.19981